Poetics of non- collection social stories by Osip Makovey (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article considers the main poetics features of Osip Makovey’s outside the collection social stories. The study of the works showed that the plot based on one case from the life of Western Ukraine villagers at the end of the ХIХ and early ХХ centuries, which enables the author to raise a number of urgent problems of the era. The writer uses a rich palette of artistic means, techniques that visually characterize his creative manner in order to express his position.
Keywords: drama aggravation; irony; contrast; problem; parallel; artistic detail; metaphor; comparison